2006
DOI: 10.1016/j.bbamem.2006.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Extra domains in secondary transport carriers and channel proteins

Abstract: "Extra" domains in members of the families of secondary transport carrier and channel proteins provide secondary functions that expand, amplify or restrict the functional nature of these proteins. Domains in secondary carriers include TrkA and SPX domains in DASS family members, DedA domains in TRAP-T family members (both of the IT superfamily), Kazal-2 and PDZ domains in OAT family members (of the MF superfamily), USP, IIA(Fru) and TrkA domains in ABT family members (of the APC superfamily), ricin domains in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 91 publications
2
47
0
Order By: Relevance
“…The topology analyses revealed that AspT does indeed have a unique topology; the protein has 10 TMs, a large hydrophilic cytoplasmic loop (about 180 amino acids) between TM5 and TM6, and N and C termini that face the periplasm. Computations using recent genome data have predicted that the AAE family is composed of membrane proteins possessing a unique membrane topology (11), and our topology analyses support this prediction.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…The topology analyses revealed that AspT does indeed have a unique topology; the protein has 10 TMs, a large hydrophilic cytoplasmic loop (about 180 amino acids) between TM5 and TM6, and N and C termini that face the periplasm. Computations using recent genome data have predicted that the AAE family is composed of membrane proteins possessing a unique membrane topology (11), and our topology analyses support this prediction.…”
supporting
confidence: 67%
“…We found 90 aspT orthologues, such as yidE and ybjL of E. coli, in 60 bacterial or archaebacterial genomes (20) (11) found in the regulatory subunit TrkA of the bacterial potassium uptake system (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the differences between multipass membrane proteins and cytoplasmic proteins seem to decrease through evolution, both regarding the hydrophobicity and U-richness, in a manner that fits the phylogenetic tree of life according to Carl Woese (18). One possible contribution to this tendency would be that membrane proteins have acquired more soluble domains through evolution (19,20), thus reducing the overall proteins' hydrophobicities and the U-richness of their encoding mRNAs. This development complicates examining possible (predicted) effects of the genome GC content on the U bias.…”
Section: Analysis Of the Distribution Of U In Membrane Protein Mrnasmentioning
confidence: 93%
“…AspT is classified as a conventional secondary transport protein and belongs to the newly classified aspartate:alanine exchanger family (TC number 2.A.81) of transporters in the system developed by Saier et al (25,26). Recently, the results of a BLAST (7) search of the nucleotide sequence of the aspT gene and the amino acid sequence of the AspT protein against current nucleotide and protein data bases, respectively, suggested that the aspartate:alanine exchanger transporters are conserved in many bacterial species (8,9). Very recently, Fukui et al (10) found SucE1, an aspartate:alanine exchanger transporter from Corynebacterium glutamicum, plays a role in the export of succinate generated during fermentation.…”
mentioning
confidence: 99%